Factores sociolaborales y nivel de estrés en enfermeras del servicio de emergencia del Hospital Regional de Trujillo entre los meses de marzo - mayo del 2010 - Vargas Sánchez, Eliana Noemí (2012)
The present study of corelational descriptive type was realised in the emergency room nurses of Regional Hospital of Trujillo between during the months of March to May of the 2010, in order to determine the existing relation between the nurses Socio Factors: Age, State Civil, Parenting, Employment Status, Salary and Years of Professional Practice, with the stress level. The sample was constituted by 25 nurses from the Emergency Service Regional Hospital of Trujillo that conformed the universal sample. The used instrument was the format - survey: Sociolabor and stress level of RN, elaborated by the author offers considering the dimensions in study. The results were reported in in graphs with percentage frequencies. In the statistic analysis it was applied the symmetrical measures ordinal by ordinal by means of the Gamma test. Of the analysis of the result one concludes: That the age of practicing nurses in the emergency service Trujillo Regional Teaching Hospital are mostly between 36 and 45 years old (44%), the (48%) are in a state married civilian, the (52%) reported having children, the (60%) are employed, the (60%) have a monthly income of less than 1 000 soles a month, the (40%) reported having more than 15 professional practice, and (60%) have a medium level of stress. Also the analysis of the data I confirm the raised hypothesis, the socio factors: Age, Marital Status, Parenting, Employment Status, Salary and Years of Professional Practice are related significantly to the taken care of quality level of according to Test Gamma (-0.613, -0.204, 0.692, -0.941, -0.984, and -0.840) respectively statistical significance (P = 0.038, P = 0.049, P = 0.049, P = 0.000, P = 0.000 and P = 0.001) respectively.